UN PROBLEMA BIEN PUESTO EN EL SENTIDO DE HADAMARD PARA UNA VIGA TERMOELÁSTICA - Luyo Sánchez, José (2006)
In this work, we present a nonlinear model of a beam of finite length, which describes the longitudinal and cross - sectional displacements, being this last phenomenon affected by gradients of temperature. We demonstrate that the system is well- posed in the sensE of Hadamardfor strong solutions.